HUBUNGAN ANTARA TINGKAT PENGETAHUAN DAN PELAKSANAAN SENAM NIFAS DENGAN KECEPATAN PROSES INVOLUSI UTERUS - Ningrum, Nyna Puspita (EMBRIO, 2012)
At the time of pregnancy and delivery ligaments, pelvis diaphragm and facia were tightly stretched, eventually rotundum became loose and cause the uterus fall backward. To recover the tissue a post natal exercises need to be done. By doing the post natal exercise enabled the stretching of muscle tone of the abdominal and perineum, recover the venous pelvic, increase the uterus contraction that can smoothly passed of the lochea and speed up involution process. The aim of research was to analyze the relation between the phase of post natal knowledge and exercises with the velocity involution of the uterus. The research applied a Quasy Experiment design. Populations involved in this research were all physiologist post natal in RB/KIA Ãƒâ€šÃ¢â‚¬Å“Endang Ãƒâ€šÃ¢â‚¬Â in Sidoarjo July 2010. The samples were collected using consecutive sampling, to analyze the relation between variables, used Chi Square test. The result showed that there was a correlation between post natal knowledge and exercises with the velocity of uterus involution where of p = 0,000 >Ã¯ÂÂ¡ = 0,05 so there is a need to increase health promotion means about post natal exercises, hence forth post natal exercise helped post partum mother to regain their condition.